Penile cancer: Perspective from a Canadian tertiary care centre - Beech, Benjamin; Izawa, Jonathan; Pautler, Stephen; Chin, Joseph; Power, Nicholas (Canadian Urological Association Journal, 2015)
Introduction: Penile squamous cell carcinoma (SCC) is rare in North America; however, the morbidity can be devastating. This analysis represents the first reported penile cancer experience at a tertiary care centre in Canada. Methods: We carried out a retrospective review of all patients who received care at our centre for penile SCC from 2005 until the present time. Epidemiological and clinical data were collected for all patients. Survival analysis was performed using Kaplan-Meier methods with log-rank test and Cox regression for univariate and multivariate analysis, respectively. Results: We identified 42 patients who were treated at our centre for penile SCC. Of these, 29% underwent excisional biopsy, 38% had partial penectomy, and 33% had total penectomy. Five patients with high-risk tumours underwent modified inguinal lymph node dissection (ILND), while 7 patients had radical ILND for clinically palpable disease. Overall, the median cancer specific survival (CSS) was undefined, with a 60% survival at 102 months. However CSS was significantly correlated to pT stage, pN stage, and tumour grade. The median follow-up was 25 months (interquartile range: 11–48). Conclusion: These findings confirm the poor CSS of patients with positive lymph nodes in penile SCC. Patients with pN0 after ILND had a durable CSS. Risk factors for penile SCC were confirmed as elevated body mass index, positive smoking history, and lack of circumcision. This first epidemiologic report on penile SCC from a Canadian tertiary care centre should be expanded to other national centres.